Diagnosis of environmental degradation in the humid slope of the Uruburetama Massif and its surroundings - Freires, Eduardo Viana (2021)
The various interventions in the Uruburetama Massif have generated a situation of degradation that compromises local economic, social and environmental sustainability. As a way of warning about the worsening of environmental problems, this research aims to make a diagnosis of environmental degradation in the humid hillside of the Uruburetama Massif / CE and its surroundings, in order to assess the impacts generated from human actions. The research methodology consisted of data acquisition, with a bibliographic review, orbital images and vector data obtaining; and carrying out field activities to recognize and identify land use and occupation and its associated impacts. Subsequently, these data and actions supported the characterization and thematic mapping of the research area. From the integration of these data, it was verified that the humid slope of the Uruburetama Massif has an advanced stage of degradation from the urban expansion and agricultural activities. The interventions occur even in the areas of permanent preservation, contrary to the Brazilian Forest Code (12.651 / 2012 Law). The state and municipal public authorities contribute to the degradation situation by making road openings without the necessary care to stabilize the slopes. There is also the absence of legislation (Installment, Zoning and Use and Occupation) that supports the process of monitoring, inspection and control of urban expansion and agricultural activities in some municipalities. Although the municipalities in the study area (Irauçuba, Itapajé, Itapipoca, Pentecoste, Tejuçuoca, Trairi, Tururu, Umirim and Uruburetama) have an environmental management body, their actions occur in a deficient manner due to lack of technical, financial and human resources, or because there are conflicts of interest when carrying out their activities integrated with other departments, such as agriculture, water resources, fishing, culture and tourism.